2010
DOI: 10.3109/00016340903578893
|View full text |Cite
|
Sign up to set email alerts
|

Developing a smoke free household initiative: an Indonesian case study

Abstract: Little research has focused on women's exposure to secondhand smoke (SHS) in LMICs, local perceptions of SHS risk to women and children, and women's attempts to limit exposure to tobacco smoke in their households. This paper describes a community based survey in Indonesia that investigated these issues as one step in a movement to initiate community wide household smoking bans. The survey found high levels of exposure to SHS, high levels of awareness among both women and men that SHS placed women and children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 6 publications
2
46
1
Order By: Relevance
“…Studies in HICs have shown how unequal power relationships and restricted living circumstances can limit women's ability to reduce exposure to SHS for themselves and their children, arising from smoking by others (usually men) in the home and workplace 65–70. In LMICs, where women's social, political and economic power is often limited, women have even less ability to protect themselves and their children from exposure to SHS from male smokers 71 72…”
Section: Limitations In Research On Girls Women and Tobaccomentioning
confidence: 99%
“…Studies in HICs have shown how unequal power relationships and restricted living circumstances can limit women's ability to reduce exposure to SHS for themselves and their children, arising from smoking by others (usually men) in the home and workplace 65–70. In LMICs, where women's social, political and economic power is often limited, women have even less ability to protect themselves and their children from exposure to SHS from male smokers 71 72…”
Section: Limitations In Research On Girls Women and Tobaccomentioning
confidence: 99%
“…Nonetheless, while active kretek smoking tends to be limited to men, children and women are likely to be exposed to secondhand smoke and may affect their health including the health of the unborn fetuses for pregnant women (WHO South East Asia Regional Office, 2009;WHO, 2010a). Although Kaufman et al (2014) and Nichter et al (2010) found a shift towards disapproval of smoking in public places in their study in Bogor and Palembang cities, Indonesia, they also found that people were hesitant to enforce the smoke-free policies when it came to asking men of status and/or community leaders to stop smoking.…”
Section: 6883 a Cross Sectional Study Of Kretek Smoking In Indonesiamentioning
confidence: 84%
“…Therefore, the child mortality rate would theoretically improve by integrating respiratory disease care into the regular health care for pediatric patients. Studies on preventing passive smoking among women have been conducted in a resource-limited setting, but the intervention was not linked with RMNCH care (36,37). Thus, further research is required to examine the effectiveness of integrating respiratory disease and RMNCH care on child health indicators.…”
Section: Discussionmentioning
confidence: 99%